Pengaruh Inflasi, Suku Bunga, Dan Produk Domestik Regional Bruto Terhadap Penyaluran Kredit Pada Bank Perkreditan Rakyat Di Indonesia (The Effect of Inflation, Interest Rate, and Gross Regional Domestic Product on Credit Distribution at Rural Banks in Ind - Khotimah, Khusnul; Toha, Akhmad; Prakoso, Aryo (e-Sospol, 2019)
AbstractThe increasing economic activity indicates that community business activities have increased. If this condition continues for a long time, the economy in Indonesia will move in a better direction. Banking has an important role in maintaining national economic stability. A way that can be done by banks is to collect and to distribute funds from the community to the community. This research was conducted to know the effect of inflation, interest rate, and GRDP (Gross Regional Domestic Product) on credit distribution at rural banks in Indonesia for the period of 2014-2017. This associative research employed a quantitative approach. A sample of 33 from the total population of 1643 was determined purposively. Data which were based on secondary data were analyzed by using multiple linear regression method. The findings indicated that inflation had no effect partially on credit distribution, whereas interest rate and GRDP had a significant effect on credit distribution. Inflation, interest rate, and GRDP affected simultaneously the credit distribution.Keywords: Credit Distribution, Inflation, Interest Rate, and GRDP